HUBUNGAN KARAKTERISTIK INDIVIDU TERHADAP IKLIM KESELAMATAN KERJA PADA DEPARTEMEN PRODUKSI 1 PERUMDA AIR MINUM TIRTA MOEDAL KOTA SEMARANG - Allisa Dzakwan Rosyada; Anik Setyo Wahyuningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Perumda Water Drinking Tirta Moedal is a regional-owned public company (BUMD) which is engaged in community services that provides clean water for the people of Semarang City and its surroundings. This study aims to analyze the relationship between respondents' characteristics in the form of age, gender, years of service, education level, position and work division with the work safety climate in the Production 1 Perumda Air Drinking Tirta Moedal Semarang City. The type of this research is analytic observational with cross sectional design with total sampling technique. The research sample was 33 respondents. The measuring instrument used is a NOSACQ-50 questionnaire. Data were analyzed by Kolmogorov-Smirnov statistical test. The results showed that Production 1 had an average work safety climate of 2.89 which was included in the sufficient category and needed improvement. Characteristics of respondents who were proven to be related to the work safety climate in this study were age, years of service and education level with p values of 0.045, 0.019, and 0.005 respectively. Efforts to improve that can be done are providing training related to occupational safety and health, especially for ages 26-45 years, working period <10 years, and education level equivalent to high school. Suggestions for this research are to improve K3 management from Top Management and make training need analysis for each category of age, years of service and education level.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//